Corporate tax planning & business tax procedures: With case studies - Singhania, Vinod K.; Singhania, Monica (New Delhi Taxmann publications (P) Ltd., 2025)
Corporate Tax Planning & Business Tax Procedures with Case Studies is an authoritative and up-to-date treatise on corporate taxation in India, blending conceptual clarity with practical application through case studies and MCQs. Centred on legitimate tax planning, it spans income-tax law, corporate tax strategies, and business tax procedures in a structured three-book format. Authored by renowned experts Dr Vinod K. Singhania and Dr Monica Singhania, the 29th Edition (2025) incorporates amendments up to 1st August 2025.